2017
DOI: 10.1007/s12195-017-0489-4
|View full text |Cite|
|
Sign up to set email alerts
|

Phase-Separated Liposomes Enhance the Efficiency of Macromolecular Delivery to the Cellular Cytoplasm

Abstract: INTRODUCTION From viruses to organelles, fusion of biological membranes is used by diverse biological systems to deliver macromolecules across membrane barriers. Membrane fusion is also a potentially efficient mechanism for the delivery of macromolecular therapeutics to the cellular cytoplasm. However, a key shortcoming of existing fusogenic liposomal systems is that they are inefficient, requiring a high concentration of fusion-promoting lipids in order to cross cellular membrane barriers. OBJECTIVES Toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 67 publications
2
39
0
Order By: Relevance
“…LNPs containing cholesterol analogs , DLin-MC3-DMA, DSPC, DMG-PEG-2000 (38.5:50:10:1.5 lipid molar ratios, respectively), and FLuc mRNA, were prepared using a standard microfluidic mixing procedure. 10,12 The structures of cholesterol analogs are shown in Figure 1A. Overall, all LNPs showed a narrow size distribution (see Figure 1B) as measured by dynamic light scattering (DLS) and >90% encapsulation efficiency ( Figure S1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LNPs containing cholesterol analogs , DLin-MC3-DMA, DSPC, DMG-PEG-2000 (38.5:50:10:1.5 lipid molar ratios, respectively), and FLuc mRNA, were prepared using a standard microfluidic mixing procedure. 10,12 The structures of cholesterol analogs are shown in Figure 1A. Overall, all LNPs showed a narrow size distribution (see Figure 1B) as measured by dynamic light scattering (DLS) and >90% encapsulation efficiency ( Figure S1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Recently, we investigated the substitution of cholesterol in LNP formulations with naturally occurring analogs with different chemical structures and the consequent effect on LNP size, mRNA encapsulation, internalization, and transfection. 10 The substitution of cholesterol (Chol) with βsitosterol (Sito) in the formulation showed a substantial improvement in cell transfection. Upon further inspection of Sito LNPs with a cryo-transmission electron microscope (cryo-TEM), we found that Sito LNPs have a faceted surface, as opposed to spherical Chol LNPs with smooth curvature, likely due to phase separation of comprising lipids, 11 and potentially, the formation of two-dimensional lipid crystals in the LNP membrane.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Membrane fusion is recognized as a potentially efficient mechanism for the delivery of macromolecular therapeutics to the cellular cytoplasm. The process of lipid membrane phase separation to concentrate binding lipids within distinct regions of the membrane surface has been shown to enhance membrane fusion [30]. In addition, recent developments on targeted lipid vesicles suggest that the formation of reversible phase-separated patterns on the vesicle surface increase target selectivity, cell uptake and overall efficacy [1,32].…”
mentioning
confidence: 99%
“…[26] In synthetic membranes,d omain formation can be readily engineered by choosing specific compositions of membrane components [27] and has been shown to enhance the efficiency of peptide-mediated fusion. [26,28] Yet, the potential of mem-brane domains to impact fusion events for the purpose of technological or therapeutic applications has to date received limited investigation [29] and merits further exploration.…”
Section: Introductionmentioning
confidence: 99%